Development of a Mobile-Based Personal Health Record for Mothers and Children Using Glide App: A Usability Study - Ombong, Deva Indri Saputri; Santoso, Dian Budi (Universitas Muhammadiyah Sidoarjo, 2024)
The increasing need for efficient personal health records (PHRs) for mothers and children has driven the development of innovative healthcare solutions. This study presents the development and evaluation of